The use of coercive measures in forensic psychiatric care: legal, ethical and practical challenges - Hui, Ada M.L.; Middleton, Hugh; Völlm, Birgit (Taylor & Francis, 2013)
The use of coercive measures, namely restraint, seclusion and involuntary medication, remain controversial methods of practice within forensic psychiatry. Ethical and moral debates surrounding the use of coercive measures are compounded by the need to balance care, safety, and security. Despite such tensions, limited research has been conducted in this area. This paper examines the prevalence of coercive measures and factors associated with their use specifically within forensic psychiatry. A systematic review was conducted and fifteen empirical studies were identified, each examining the use of coercive measures in forensic inpatient psychiatry, reported in papers published between January 1980 and January 2012. Findings suggest that patients who are younger or newly admitted tend to be secluded most often. Findings relating to gender, ethnicity and patient diagnoses, however, are equivocal. Patients tend to perceive experiences of coercive measures negatively. Staff perceptions however, appear to be determined by their role in governing or practicing coercive interventions. Findings are discussed in light of variations in hospital settings, policies and sociocultural traditions. While the uses of coercive measures appear to be influenced by a combination of all patient, staff, and environmental factors, further research is required to explore each of these aspects in greater detail.